2001
DOI: 10.1002/1521-3862(200107)7:4<167::aid-cvde167>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

CVD of SiC from Methyltrichlorosilane. Part I: Deposition Rates

Abstract: The CVD of silicon carbide from methyltrichlorosilane (MTS) was studied at various surface area/volume ratios, using an MTS/H 2 mixture of 1:4. The total pressure was 90 kPa; the temperature was varied from 800 C to 1100 C at residence times of 0.9 s and 0.4 s. Steady-state deposition rates were determined as a function of reactor length. The deposition rate as a function of temperature, investigated at a low surface area/volume ratio, shows strong and weak intermediate maxima at temperatures of about 900 C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 25 publications
(51 reference statements)
0
40
0
Order By: Relevance
“…[1] These temperatures correspond to a residence time of 0.9 s; the rate maxima being shifted to higher temperatures if the residence time is decreased or the flow rate is increased. Furthermore, it was shown that the rate maxima only exist at a low [A S /V R ] ratio.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1] These temperatures correspond to a residence time of 0.9 s; the rate maxima being shifted to higher temperatures if the residence time is decreased or the flow rate is increased. Furthermore, it was shown that the rate maxima only exist at a low [A S /V R ] ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Figure 4 may be used to determine individual deposition rates of SiC and Si from the measured or overall rates reported in Figure 1 of Part I. [1] They are presented in Figure 6 for the low [A S /V R ] ratio of 0.78 mm ±1 , and in Figure [1] ). This presentation was chosen to demonstrate changes of deposition rate along the substrate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations